Green synthesis of zinc oxide nanoparticles utilizing extract from Garcinia mangostana leaves: Characterization and optimization of calcination temperature (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aims to synthesize eco-friendly zinc oxide nanoparticles (ZnO NPs) by utilizing Garcinia mangostana leaf extract and assess the characteristics of ZnO NPs produced throughout different calcination temperatures (300°C, 400°C, 500°C, and 600°C). Materials and Methods: An evaluation was conducted to analyze ZnO NPs using an aqueous extract of G. mangostana leaf bioreductor at different calcination temperatures. The analysis involved the use of a particle size analyzer (PSA), a scanning electron microscope (SEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Results: The PSA and SEM indicated that the ZnO NPs had an average particle size ranging from 641.97 nm to 915.94 nm. Furthermore, the nanoparticles were found in both individual nanoforms and agglomerated forms. The EDX study indicated that the primary constituents of the ZnO NPs were zinc and oxygen. Additionally, the XRD examination demonstrated a distinct peak at 2θ = 36.25°, confirming the presence of a crystalline ZnO structure. The crystal size was determined to be between 40.98 nm and 46.92 nm. An FTIR spectroscopic study verified the existence of ZnO vibrations at distinct wavelengths as well as the absorption peak of the -OH functional group within the range of 3330.58 nm–3415.04 nm. Conclusion: The findings suggest that ZnO NPs produced utilizing the aqueous extract of G. mangostana leaves as a bioreductor can be synthesized at a temperature of 300°C, resulting in a lower particle size compared to those generated at 600°C.J. Adv. Vet. Anim. Res., 11(3): 573-582, September 2024http://doi.org/10.5455/javar.2024.k807